2012
DOI: 10.1007/s11739-012-0885-7
|View full text |Cite
|
Sign up to set email alerts
|

Verification of correct central venous catheter placement in the emergency department: comparison between ultrasonography and chest radiography

Abstract: In 210 consecutive patients undergoing emergency central venous catheterization, we studied whether an ultrasonography examination performed at the bedside by an emergency physician can be an alternative method to chest X-ray study to verify the correct central venous catheter placement, and to identify mechanical complications. A prospective, blinded, observational study was performed, from January 2009 to December 2011, in the emergency department of a university-affiliated teaching hospital. Ultrasonography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 46 publications
0
39
0
3
Order By: Relevance
“…Vatansever [10] proposed fetal neuroimaging study that provide normal posterior fossa growth trajectories during the second and third trimesters of pregnancy via semi-automatic segmentation of reconstructed fetal brain MR images and to assess common cerebellar malformations in comparison with the reference data. Anobetti [11] showed a high correlation between two modalities to identify possible malpositioning of a catheter resulting from cannulation of central veins, and its complications. The less time required to perform ultrasonography allows earlier use of the catheter for the administration of acute therapies that can be life-saving for the critically ill patients.…”
Section: Introductionmentioning
confidence: 99%
“…Vatansever [10] proposed fetal neuroimaging study that provide normal posterior fossa growth trajectories during the second and third trimesters of pregnancy via semi-automatic segmentation of reconstructed fetal brain MR images and to assess common cerebellar malformations in comparison with the reference data. Anobetti [11] showed a high correlation between two modalities to identify possible malpositioning of a catheter resulting from cannulation of central veins, and its complications. The less time required to perform ultrasonography allows earlier use of the catheter for the administration of acute therapies that can be life-saving for the critically ill patients.…”
Section: Introductionmentioning
confidence: 99%
“…This visualization of the echogenic agitated saline allowed for confirmation of correct CVC placement in an average of 10 minutes with 96% sensitivity. Zanobetti et al [14] used a more complex ultrasound protocol with multiple views and also observed correct CVC placement in an average of 5 minutes with 94% sensitivity. Although requiring more views, these studies are also promising for rapid confirmation of supra-diaphragmatic CVC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, multiple studies have demonstrated that with a combination of ultrasound views and injectable materials, POCUS may be able to provide earlier and correct CVC positioning in the superior vena cava. [7,13,14] Vezzani et al [13] illustrated that the use of contrast enhanced, agitated saline could be used to confi rm placement of CVC. This visualization of the echogenic agitated saline allowed for confirmation of correct CVC placement in an average of 10 minutes with 96% sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the result of current study they concluded that there is high correlation between aforementioned modalities in identifying possible malpositioning of the catheter. Furthermore, less time is required to perform ultrasonography comparing to CXR [21].…”
Section: Discussionmentioning
confidence: 99%